Children’s advertising in the Arts and Media Education of future teachers: Educational experience based on visual analysis and creation - Marfil-Carmona, Rafael; Morales-Caruncho, Xana; Chacón-Gordillo, Pedro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This research, carried out with 62 students of the degree in Pre-Primary Education at the University of Granada, focuses on the development of a advertising counter-narrative project in which analysis and critical thinking are combined with creative and expressive skills, through the reinterpretation of children’s advertising campaigns. Both the annotation records, in the framework of participant observation, and the analysis of the resulting images, allow us to affirm that advertising is an ideal framework for work in the interdisciplinary space between Arts and Media Education, highlighting the concerns of future teachers, such as health, gender equality and education in values.